正在加载图片...
G()=+(1-y)H-H U(K+1) (2-82) (2-83) N=N-N f=c-I+2 Ny=f+1=(-1+2)=c+2 N"=∑N+N-N (3-2) (3-3a) ax (3-3b) L AD (3-5) =a,·a N1·C (3-7) aA=1·a,·a N lga (3-10( ) ( ) G =HV + 1− HL − HF (2-81) ( ) (K ) V L K F L H H H H         − − = +1  (2-82) ( ) ( ) ( ) ( ) K K K  = + d − + 计 1 (2-83) Ni = Nv − Nc (3-1) f = c − + 2 Nv = f +1= (c −1+ 2) = c + 2 =  + − i N N N N u r c e i u i (3-2) ( )  = + − m 1 i i i,D m R x    (3-3a)  = − 1- q i i i,F    x (3-3b) 1 D 1 1         =         =         B A B A B A x x x x y y  (3-4) A,2 A,1 DxA,D V2 y = L1 x − (3-5) 1         =         B A B A x x y y 2 (3-6) B W A N B A x x x x         = • • •         1  2  3 N-1  D (3-7)   1 1 2 3 N-1 N N       AB = • • • AB m lg lg                          = B W A B A x x x x N D (3-8) 3   D  W  F 平均 = • • (3-9)   D  W 平均 = • (3-10)
<<向上翻页向下翻页>>
©2008-现在 cucdc.com 高等教育资讯网 版权所有